Unveiling the Lecturers’ and Students' Needs in English for Public Administration Program: Essential Vocabulary Topics, Instructional Methods, and Learning Challenges - Misnawati, Misnawati; Atmowardoyo, Haryanto; Sulaiman, Iskandar; Yusriadi, Yusriadi; Rahman, Abdul (Register Journal, 2024)
The lack of attention given in scholarly research to the particular requirements of Public Administration has resulted in a knowledge deficit to suit students' interests in this discipline. Prior research has predominantly examined the quantitative dimensions of vocabulary acquisition while neglecting to adequately consider the qualitative aspects, including comprehension and language use, in a contextually appropriate manner. This study aims to fill in these knowledge deficits by investigating vocabulary themes or topics related to Public Administration, evaluating existing instructional approaches and challenges, and suggesting enhancements to bolster students' English language proficiency in Public Administration. The study employs a qualitative methodology, including an open-ended questionnaire and in-depth interviews with four lecturers and 100 first-year students from three universities in South Sulawesi, Indonesia. The findings revealed that the English for Public Administration curriculum requires a diverse vocabulary of topics from administration, management, and governance to more nuanced areas such as economics, finance, taxation, social and ethics, technology and digitalization, leadership, and regulation and law. Various teaching and assessment strategies regarding instructional methods, including interactive and collaborative methods, technology integration, and contextual learning, suggest the importance of engaging students with diverse and practically relevant content to prepare them for the multifarious nature of public sector roles. Students, however, found some challenges in the complexity of the Public Administration vocabulary, highlighting the need for tailoring educational strategies, such as project-based learning and vocabulary reinforcement techniques, to overcome these obstacles. The study's findings have substantial implications for policymakers, curriculum developers, and lecturers specializing in public administration education.